Effects of Different Stocking Densities on the Growth, Antioxidant Status, and Intestinal Bacterial Communities of Carp in the Rice–Fish Co-Culture System - Weixu Diao; Rui Jia; Yiran Hou; Jianyou Gong; Liqiang Zhang; Bing Li; Jian Zhu (Fishes, 2024)
Common carp (Cyprinus carpio) is a freshwater fish commonly farmed in rice fields, yet there were few studies on the intestinal functions and microbial community structure of common carp in the rice–carp co-culture system. Therefore, this study aimed to explore the effects of different stocking densities on the growth, antioxidant status, and intestinal bacterial composition of common carp in this system. This study was divided into three different stocking densities, including low density (LD, 10 fish, 52.9 g/m2), medium density (MD, 20 fish, 105.8 g/m2), and high density (HD, 30 fish, 158.7 g/m2), with a culturing period of 60 days. The results indicated that HD treatment inhibited the growth of common carp, as evidenced by the reduced final weight, WG, and SGR. In serum, the TG content in the HD group and the Cor content in the MD group were significantly increased. Meanwhile, HD treatment induced oxidative stress, manifesting specifically as increased SOD and CAT activities in the intestine or serum while reducing Gpx, GSH, and T-AOC in the serum. The 16S rDNA analysis indicated that the Simpson and Shannon indices of intestinal microbiota in the HD group were significantly higher than those in the LD group. At the phylum level, Proteobacteria, Cyanobacteria, and Firmicutes were dominant microbial communities in two groups. In addition, there was a significant difference between the two groups in the abundances of Actinobacterota and Bifidobacterium. Based on growth performances, biochemical indicators, and microbial diversity in rice–carp co-culture, low density (52.9 g/m2) may be more suitable in the rice–carp co-culture systems. In summary, this study contributes to a better understanding of common carp response to different stocking densities in the rice–carp co-culture system.